2004
DOI: 10.1016/j.neuron.2004.06.018
|View full text |Cite
|
Sign up to set email alerts
|

The Slit Receptor Rig-1/Robo3 Controls Midline Crossing by Hindbrain Precerebellar Neurons and Axons

Abstract: During development, precerebellar neurons migrate dorsoventrally from the rhombic lip to the floor plate. Some of these neurons cross the midline while others stop. We have identified a role for the slit receptor Rig-1/Robo3 in directing this process. During their tangential migration, neurons of all major hindbrain precerebellar nuclei express high levels of Rig-1 mRNA. Rig-1 expression is rapidly downregulated as their leading process crosses the floor plate. Interestingly, most precerebellar nuclei do not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
228
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(255 citation statements)
references
References 50 publications
24
228
1
2
Order By: Relevance
“…Bioreactor technology can potentially be used for combination treatment with encapsulated cells overexpressing multiple anti-invasive, antiproliferative and proapoptotic molecules. Marillat et al (2004) have demonstrated a role for Rig1/Robo3 in controlling midline crossing of hindbrain precerebellar neurons and axons. Human patients with horizontal gaze palsy with progressive scoliosis (HGPPS) were reported to have mutations in Rig1/ Robo3, and functional studies have shown defects in commissural hindbrain projections and pontine nuclei (Jen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Bioreactor technology can potentially be used for combination treatment with encapsulated cells overexpressing multiple anti-invasive, antiproliferative and proapoptotic molecules. Marillat et al (2004) have demonstrated a role for Rig1/Robo3 in controlling midline crossing of hindbrain precerebellar neurons and axons. Human patients with horizontal gaze palsy with progressive scoliosis (HGPPS) were reported to have mutations in Rig1/ Robo3, and functional studies have shown defects in commissural hindbrain projections and pontine nuclei (Jen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Antisense riboprobes were labeled with digoxigenin-11-D-UTP (Roche Diagnostics) as described previously (Marillat et al, 2002), by in vitro transcription of mouse or rat cDNAs encoding Slit1, Slit2, Slit3, Robo1, Robo2 (Brose et al, 1999), Robo3 (Marillat et al, 2004), Brn3.2, TAG-1, Pax6 (de Diego et al, 2002, Barhl1 (Li et al, 2004), and Er81 (Zhu and Guthrie, 2002). Tissue sections and whole-mount embryos were hybridized with digoxigenin-labeled riboprobes as described previously (Marillat et al, 2002(Marillat et al, , 2004.…”
Section: Methodsmentioning
confidence: 99%
“…Netrin-1 was shown to attract all precerebellar neurons toward the midline (Bloch-Gallego et al, 1999;Yee et al, 1999;Causeret et al, 2002). We showed previously that the receptor Rig1/Robo3 (hereafter referred to as Robo3) has a major function in this process (Marillat et al, 2004) because precerebellar neurons are unable to cross the midline in Robo3 Ϫ/ Ϫ mutant embryos and send their axons into the ipsilateral cerebellum. Robo3 plays a similar role in spinal cord commissural axons .…”
Section: Introductionmentioning
confidence: 99%
“…Qu'en est-il des autres axones commissuraux du cerveau? Notre équipe a étudié plusieurs populations de neurones du tronc cérébral qui envoient des axones dans le cervelet, d'où leur nom de neurones précérébelleux, et ont un rôle important dans le contrôle des mouvements et de l'équilibre [8]. Tous ces neurones projettent leurs axones à travers la plaque du plancher.…”
Section: Le Code De La Route Des Axones Se Compliqueunclassified
“…Nous avons montré que tous les neurones précérébelleux expriment fortement Robo-3/Rig-1 jusqu'à ce que leurs axones ou leurs corps cellulaires aient croisé la ligne médiane. Chez les souris défi-cientes en Robo-3, ni les axones des neurones précérébelleux, ni leurs corps cellulaires ne traversent la plaque du plancher [8]. Le phénotype est donc identique à celui qui est observé pour les axones de la moelle épinière.…”
Section: Le Code De La Route Des Axones Se Compliqueunclassified